Karsinoma Kolon Sigmoid dengan Metastasis Hepar: Analisis Klinis, Diagnostik, dan Penatalaksanaan - Khalishah, Iffatunnada; Fathurrahman, Yusmaidi; Pestalozi, George (CV. Jasa Sukses Abadi, 2026)
Colorectal cancer is one of the most common cancers affecting the colon or rectum, with prevalence continuing to increase. In Indonesia, this cancer is ranked fourth with more than 34,000 new cases in 2020. The main risk factors for colorectal cancer include a diet high in fat and low in fiber, age over 50 years, and a family history of colorectal cancer. Symptoms often involve changes in bowel patterns, blood in the stool, abdominal pain, and unexplained weight loss. In more advanced cases, intestinal obstruction or metastasis to other organs, including the liver, may occur. This article reviews a case of a 57-year-old female patient who came with complaints of difficulty defecating accompanied by blood in the stool, abdominal pain, and weight loss. Based on the results of physical examination, laboratory, and other supporting examinations such as colonoscopy and histopathology, colorectal cancer with liver metastases was diagnosed. Treatment is carried out with fluid therapy, symptomatic treatment, and Hartmann procedure surgery to remove the sigmoid colon mass. A patient's prognosis is influenced by the stage of the cancer, with advanced stages having a poor prognosis. This research aims to increase knowledge about colorectal cancer and emphasize the importance of early detection and a multidisciplinary approach to treating colorectal cancer.